Anti-Inflammatory Effect of 1,3,5,7-Tetrahydroxy-8-isoprenylxanthone Isolated from Twigs of Garcinia esculenta on Stimulated Macrophage - Zhang, Dan-Dan (Mediators Inflamm, 2015)
Garcinia Linn. plants having rich natural xanthones and benzophenones with anti-inflammatory activity attracted a great deal of attention to discover and develop them as potential drug candidates. Through screening targeting nitric oxide accumulation in stimulated macrophage, we found that 1,3,5,7-tetrahydroxy-8-isoprenylxanthone (TIE) had potential anti-inflammatory effect. To understand how TIE elicits its anti-inflammatory activity, we uncovered that it significantly inhibits the production of nitric oxide (NO) and prostaglandin E2 (PGE2) in LPS/IFNγ-stimulated RAW264.7 cells. In further study, we showed that TIE reduced the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), two key molecules responsible for the production of NO and PGE2 during inflammation progress. Additionally, TIE also suppressed the expression of inflammatory cytokines IL-6, IL-12, and TNF-α. TIE-led suppression in iNOS, COX-2, and cytokines production were probably the consequence of TIE's capability to block ERK and p38MAPK signaling pathway. Moreover, TIE blocked activation of nuclear factor-kappa B (NF-κB) as well as NF-κB regulation of miR155 expression. Our study suggests that TIE may represent as a potential therapeutic agent for the treatment of inflammatory diseases.